Exploring the interplay between metabolic power and equivalent distance in training games and official matches in soccer: a machine learning approach - Manzi, V.; Savoia, C.; Padua, E.; Edriss, S.; Iellamo, F.; Caminiti, G.; Annino, G. (Frontiers in Physiology, 2023)
Introduction: This study aimed to explore the interplay between metabolic power (MP) and equivalent distance (ED) and their respective roles in training games (TGs) and official soccer matches. Furthermore, the secondary objective was to investigate the connection between external training load (ETL), determined by the interplay of metabolic power and equivalent distance, and internal training load (ITL) assessed through HR-based methods, serving as a measure of criterion validity.